THE MODERATE SIDE OF ISLAMIC EDUCATION IN THE ARCHIPELAGO - Nur Jihadi (TAWASUT, 2025)
Islamic education emerged and developed since Islam began to enter Indonesia brought by wandering Sufis or traders from the Middle East. In the spread of Islam in various regions of Indonesia, simply includes Islamic education through Islamic da'wah that is delivered. The purpose of writing this paper is to offer an idea about the metamorphosis of Islamic education in the archipelago. That metamorphosis occurs in two aspects of Islamic education, namely institutional and learning. The institutional metamorphosis of Islamic education is a study of the dynamics of the development of Islamic boarding schools, madrasah schools, and Islamic Religious Higher Education in Indonesia. While the metamorphosis of learning occurs in three domains, namely experimental science, integration of scholars and scientists, and initiating authentic Islamic Education Management.The findings suggest that pesantren can play a significant role in promoting moderation in education by incorporating diverse perspectives, encouraging critical thinking, and nurturing empathy. This study contributes to the ongoing debate on the role of religious education in promoting social harmony and highlights the potential of pesantren as a model for moderating education in diverse